2000
DOI: 10.1016/s0377-0273(00)00195-5
|View full text |Cite
|
Sign up to set email alerts
|

The Canary Islands origin: a unifying model

Abstract: A new model, partially based on the three most widely cited previous hypotheses, is proposed to explain the genesis of the Canary Islands. From the hotspot hypothesis it retains the notion that the islands originated from a thermal anomaly in the mantle. From the propagating fracture hypothesis it takes the critical role of regional fractures in the onset of magmatism. The uplifted block hypothesis contributes with the notion that the islands are in their present freeboard attitude due to the action of tectoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 137 publications
5
140
0
3
Order By: Relevance
“…Other alternative models propose that the volcanic activity of the Canary Islands revives by processes repeatedly occurring over a period of time (i.e. Anguita and Hernán, 2000). These models are more consistent with the recorded ages than those proposing a single one-way migration of the initiation of the magmatism.…”
Section: Chronological Evolution Of the Canarian Volcanismmentioning
confidence: 89%
See 1 more Smart Citation
“…Other alternative models propose that the volcanic activity of the Canary Islands revives by processes repeatedly occurring over a period of time (i.e. Anguita and Hernán, 2000). These models are more consistent with the recorded ages than those proposing a single one-way migration of the initiation of the magmatism.…”
Section: Chronological Evolution Of the Canarian Volcanismmentioning
confidence: 89%
“…On the other hand, the temporal evolution of the volcanic activity on each one of the Canary Islands has always been an important key in the understanding of the archipelago, from the early models of Wilson (1973), Morgan (1971) and Anguita and Hernán (1975), to the most recent of Araña and Ortiz (1991), Hoernle and Schmincke (1993), Carracedo et al (1998), Anguita and Hernán (2000), Geldmacher et al (2001) and Guillou et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous inconsistencies between the evolution of the Canary Islands and the classical hot spot scheme have been reported by Hoernle and Schmincke (1993). To explain these differences, these authors suggested that the Canary Islands plume corresponds to a "blob type" (Allègre et al, 1984) hot spot, whereas others (Anguita and Hernán, 2000) proposed a unifying model partly reconciling three of the historically cited hypotheses, thus giving more weight to the regional tectonics. Whatever the scenario, it seems now widely accepted that volcanism in the Canary Islands cannot be attributed to a classical hotspot alone and is not completely independent of the regional tectonics.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Regional models for the origin of eastern Central-Atlantic intraplate volcanism can be grouped into non-plume models (e.g., Schmincke 1982;King and Anderson 1998;Anguita and Hernán 2000;King and Ritsema 2000), plume models (e.g., Burke and Wilson 1972;Duncan 1984;Hoernle and Schmincke 1993a, b;Hoernle 1998;Carracedo 1994;Mata et al 1998;Widom et al 1999;Gurenko et al 2006), or any combination of both (e.g. Carracedo et al 1998;Geldmacher et al 2005Geldmacher et al , 2006aSchmincke and Sumita 2010).…”
Section: Geological Overview and Summary Of Previous Workmentioning
confidence: 99%